Alumina powder and its preparation method and application

By grafting an amide group-containing silane coupling agent on the surface of the alumina powder, the problem of poor affinity of alumina powder in ceramic slurry is solved, the dispersion of the powder and the strength of the ceramic base are improved, and the effect of the achievement of the effect of the alumina powder is achieved. Higher product yield and cutting accuracy.

CN118619317BActive Publication Date: 2025-02-25CHAOZHOU THREE CIRCLE GRP CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410679161.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-29
Publication Date
2025-02-25
Estimated Expiration
2044-05-29

AI Technical Summary

Technical Problem

The alumina powder has poor affinity with organic components in ceramic slurry, resulting in low strength and easy warping of the packaging base, and the product yield decreases. At the same time, the viscosity of the ceramic slurry is difficult to control, affecting the molding and cutting accuracy.

Method used

Grafting an amide group-containing silane coupling agent on the surface of the alumina powder can improve the hydrophilicity of the alumina powder and its affinity with organic resin by hydrolyzing and joining hydrophobic groups, thereby improving the dispersion of the powder and strength of ceramic base.

Benefits of technology

The dispersion of alumina powder in the slurry is significantly improved, the agglomeration is avoided, the strength and dimensional accuracy of the packaging base are improved, and the warpage and operation difficulty are reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004865110030000031
    Figure BDA0004865110030000031
  • Figure BDA0004865110030000032
    Figure BDA0004865110030000032
  • Figure BDA0004865110030000041
    Figure BDA0004865110030000041
Patent Text Reader

Abstract

The present invention belongs to the field of ceramic technology, and specifically discloses an alumina powder and a preparation method and application thereof. The present invention grafts an amide-containing silane coupling agent on the surface of alumina, which can improve the dispersibility of the alumina powder in the slurry and avoid agglomeration, thereby improving the strength of the package base product and reducing the warpage.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of ceramics, and in particular relates to an aluminum oxide powder and a preparation method and application thereof. Background Art

[0002] Alumina has the advantages of high strength, excellent thermal conductivity, good insulation, heat shock resistance and chemical corrosion resistance, and is widely used as a packaging base for electronic components such as semiconductor components and crystal oscillators. Usually, the preparation of the packaging base requires a certain proportion of alumina powder, a binder, and a dispersant to be mixed into a ceramic slurry, which is then obtained through tape casting, stamping cutting, and high-temperature sintering. However, in the ceramic slurry, the alumina powder has strong hydrophilicity, is easy to agglomerate, and has poor affinity with organic components such as binders or dispersants in the slurry, which often leads to low strength and easy warping of the packaging base, which in turn leads to a decrease in product yield. In addition, the ceramic slurry needs to maintain a suitable viscosity range. If the viscosity of the ceramic slurry is too low, it is not easy to form; if the viscosity of the ceramic slurry is too high, the green body after tape casting has a large viscosity, and it is not easy to peel off from the base tape after tape casting, and it is not easy to cut during cutting. The cutting process is prone to adhesion, resulting in low dimensional accuracy and high difficulty in operation.

[0003] Therefore, there is still a need to develop an alumina powder that has good affinity with organic components in the ceramic slurry and can maintain a suitable viscosity of the overall ceramic slurry. Summary of the invention

[0004] In view of the problems in the prior art mentioned above that alumina powder has poor affinity with organic components in ceramic slurry, the present invention provides an alumina powder and a preparation method and application thereof.

[0005] To achieve the above purpose, the following technical solutions are specifically included:

[0006] In one aspect, the present invention provides a method for preparing aluminum oxide powder, comprising the following steps:

[0007] (1) mixing an amino group-containing silane coupling agent with a first solvent, and then adding a carboxylic acid ester to react under the protection of an inert gas to obtain an amide group-containing silane coupling agent;

[0008] (2) The amide-containing silane coupling agent, the second solvent, and aluminum oxide are sequentially mixed and subjected to grafting reaction to obtain the aluminum oxide powder.

[0009] The present invention grafts an amide-containing silane coupling agent on the surface of an alumina powder. The amide-containing silane coupling agent is easily hydrolyzed to form a silanol group, and the amide group is conducive to the bonding of hydrophobic groups and the grafting modification on the surface of the alumina powder, so that the hydrophilicity of the alumina is reduced, the affinity of the alumina powder with the organic resin is significantly improved, and the combination between the alumina powder and the interface layer of the organic resin (such as acrylic resin) is facilitated, the powder is prevented from agglomerating, the particle size of the alumina powder is reduced, and the dispersibility of the alumina powder in the slurry is significantly improved.

[0010] Preferably, in step (1), the amino-containing silane coupling agent includes at least one of 3-aminopropyltrimethoxysilane, N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane, aminoethylaminomethylmethyldiethoxysilane, and N-(6-aminohexyl)aminomethyltriethoxysilane, and the carboxylic acid ester includes at least one of isobutyl hexanoate, n-butyl decanoate, and isobutyl dodecanoate.

[0011] Preferably, in step (1), the molar ratio of the amino-containing silane coupling agent to the carboxylic acid ester is 1:(0.5-1.5).

[0012] Preferably, in step (1), the molar ratio of the amino-containing silane coupling agent to the first solvent is (1-2):1.

[0013] Preferably, in step (1), the reaction temperature is 75-90° C., and the reaction time is 4-6 h.

[0014] Preferably, in step (1), the first solvent comprises at least one of n-butanol, isopropanol and ethanol.

[0015] Preferably, in step (1), the inert gas includes at least one of nitrogen, argon and helium.

[0016] Preferably, in step (2), the mass ratio of the amide-containing silane coupling agent to aluminum oxide is (0.001-0.007):1.

[0017] Further preferably, in step (2), the mass ratio of the amide-containing silane coupling agent to aluminum oxide is (0.001-0.005):1.

[0018] Under the above mass ratio of the amide-containing silane coupling agent and alumina, the dispersibility of the powder in the slurry can be further controlled by controlling the ratio of the silane coupling agent to alumina, thereby further improving the strength of the ceramic base.

[0019] Preferably, in step (2), the grafting reaction is carried out under ball milling conditions, the grafting reaction time is 2-3 hours, and the rotation speed of the ball mill is 200-400 rpm.

[0020] Preferably, in step (2), the mass ratio of the second solvent to the aluminum oxide is (0.46-0.52):1.

[0021] Preferably, in step (2), the second solvent comprises at least one of acetone, ethanol, isopropanol and terpineol.

[0022] The present invention also provides an aluminum oxide powder, wherein a silane coupling agent containing an amide group is grafted onto the surface of the aluminum oxide powder, and the chemical structural formula of the silane coupling agent containing an amide group is shown in the following formula I:

[0023]

[0024] Wherein, R1, R2, and R3 are each selected from one of H atom, alkane group, and alkoxy group, at least one of R1 to R3 is an alkoxy group; R is selected from one of straight chain or branched alkane group and aromatic group, and X is selected from one of alkane group and amino-substituted alkane group.

[0025] Preferably, the chemical structural formula of the silane coupling agent containing an amide group is as shown in Formula II below:

[0026]

[0027] Among them, R1, R2, and R3 are each selected from one of H atom, alkane group, and alkoxy group, and at least one of R1 to R3 is an alkoxy group; R4 and R5 are each selected from one of straight chain or branched alkane group, and R is selected from one of straight chain or branched alkane group and aromatic group.

[0028] The surface of the aluminum oxide powder of the above-mentioned formula II structure is grafted with a silane coupling agent containing both an amide group and an amino group. The amino group further promotes the hydrolysis of the alkoxy group on the silicon atom into an alcohol group, which is more conducive to grafting on the surface of the aluminum oxide powder.

[0029] Preferably, the number of carbon atoms in R1 is 1-2, the number of carbon atoms in R2 is 1-2, the number of carbon atoms in R3 is 1-2, the number of carbon atoms in R4 is 1-5, the number of carbon atoms in R5 is 1-5, and the number of carbon atoms in R is 5-12.

[0030] Preferably, the ratio of the number of carbon atoms in R4, R5 and R is n(R4):n(R5):n(R)=(0.08-0.6):(0.1-6):1.

[0031] Further preferably, the ratio of the number of carbon atoms in R4, R5 and R is n(R4):n(R5):n(R)=(0.08-0.6):(0.1-0.6):1.

[0032] The larger the number of carbon atoms in the terminal R group, the better to improve the hydrophobicity and the affinity between the alumina powder and the resin. When the larger the number of carbon atoms in the terminal R group, the steric hindrance effect can also be used to inhibit the formation of Si←N coordination bonds between nitrogen atoms and silicon atoms, thus preventing them from affecting the grafting of silane and alumina powder.

[0033] Preferably, the relative molecular mass of the silane coupling agent is 300-500.

[0034] When the relative molecular mass of the silane coupling agent is between 300 and 500, the hydrophobicity of the surface of the alumina powder can be improved, and the resin has good wettability to the alumina powder. At the same time, the silane coupling agent is easy to decompose during subsequent sintering and will not cause residual carbon deposition.

[0035] Preferably, the silane coupling agent containing an amide group comprises at least one of the following chemical structural formulas:

[0036]

[0037]

[0038] The present invention also provides an application of the alumina powder in the preparation of a ceramic packaging base. The surface of the alumina powder is grafted with an amide-containing silane coupling agent, which can significantly improve the dispersibility of the slurry for preparing the ceramic packaging base and improve the strength of the ceramic packaging base. At the same time, the alumina grafted with an amide-containing silane coupling agent decomposes silicon oxide during the debinding sintering process and can also act as a sintering aid, thereby inhibiting grain growth, reducing the sintering temperature, promoting sintering, and further improving the strength of the packaging base.

[0039] Preferably, the method for preparing the ceramic package base comprises the following steps:

[0040] (1) mixing the alumina powder, sintering aid, dispersant, colorant, resin, and third solvent and ball milling to obtain a ceramic slurry;

[0041] (2) tape-casting the ceramic slurry to obtain a ceramic green body;

[0042] (3) according to the structural requirements of different ceramic layers of the package base, the ceramic green sheets of each layer are respectively opened, filled, and conductive patterns are printed, and then the ceramic green sheets of each layer are laminated together and cut into a plurality of ceramic package base green sheets;

[0043] (4) Sintering the ceramic package base green body into porcelain, and plating a metal layer on the exposed conductive pattern to obtain a package base.

[0044] Preferably, the mass ratio of the alumina powder, sintering aid, dispersant, colorant, resin and the third solvent is: 1: (0.065-0.075): (0.5-0.6): (1.5-2.0): (7-9): (1-2).

[0045] Preferably, the sintering aid includes at least one of zirconium oxide, magnesium oxide, yttrium oxide, chromium oxide and titanium oxide.

[0046] Preferably, the dispersant comprises at least one of oleic acid, triolein, and phosphate ester.

[0047] Preferably, the colorant includes at least one of a transition metal compound and a lanthanide metal compound.

[0048] Preferably, the resin includes at least one of polyvinyl butyral, acrylic resin, methyl cellulose, ethyl cellulose, and phenolic resin.

[0049] Preferably, the third solvent includes at least one of acetone, ethanol, isopropanol and terpineol.

[0050] Preferably, the sintering temperature is 1300-1400° C., and the sintering time is 4-6 hours.

[0051] Compared with the prior art, the present invention has the following beneficial effects: by grafting an amide-containing silane coupling agent on the surface of alumina, the present invention can improve the dispersibility of alumina powder in the slurry and avoid agglomeration, thereby improving the strength of the packaging base product and reducing the warpage. DETAILED DESCRIPTION

[0052] In order to better illustrate the purpose, technical scheme and advantages of the present invention, the present invention will be further described below through specific examples. The test methods used in the examples and / or comparative examples are conventional methods unless otherwise specified; the materials, reagents, etc. used can be obtained from commercial channels unless otherwise specified.

[0053] Example 1

[0054] A method for preparing aluminum oxide powder comprises the following steps:

[0055] S1, 3-aminopropyltrimethoxysilane and an equal molar amount of n-butanol are mixed, and the mixture is stirred under a nitrogen atmosphere, and then an equal molar amount of isobutyl hexanoate is added to the aminopropyltrimethoxysilane, and the mixture is refluxed at 90° C. for 5 h to obtain pentylamidopropyltrimethoxysilane;

[0056] S2, mixing pentylamidopropyltrimethoxysilane, acetone and alumina powder, and reacting them under ball milling at 300 rpm for 2 hours to obtain alumina powder grafted with hexanoic acid amide propyltrimethoxysilane;

[0057] Among them, the mass ratio of pentylamidopropyltrimethoxysilane, acetone and alumina powder is 0.005:0.5:1.

[0058] A method for preparing a ceramic package base comprises the following steps:

[0059] (1) mixing the above-mentioned alumina powder grafted with amylamidopropyltrimethoxysilane, a sintering aid, a dispersant, a colorant, a resin and a third solvent in a mass ratio of 1:0.07:0.5:1.5:8:2 and ball milling to obtain a ceramic slurry;

[0060] The sintering aid is a mixture of zirconium oxide, magnesium oxide and yttrium oxide in a mass ratio of 1:0.5:0.2, the colorant is chromium oxide, the resin is acrylic resin, the dispersant is triolein, and the third solvent is a mixture of acetone and isopropanol in a mass ratio of 1:1;

[0061] (2) tape-casting the ceramic slurry to obtain a ceramic green body, and according to the structural requirements of different ceramic layers of the packaging base, respectively perform hole opening, hole filling, and printing of conductive patterns on each layer of the ceramic green body, and then stack the layers of the ceramic green body together and cut them into a plurality of ceramic packaging base green bodies;

[0062] (3) The ceramic package base green body is sintered at 1350° C. for 5 hours to form porcelain, and a metal layer is plated on the exposed conductive pattern to obtain a package base product.

[0063] Embodiment 2-8

[0064] Compared with Example 1, Examples 2-8 differ in that the types of aminosilane coupling agents and / or carboxylic acid esters in step S1 are different, and the specific types are shown in Table 1.

[0065] Examples 9-17

[0066] Compared with Example 2, Examples 9-17 differ in that in step S2, the mass ratio of the amide-containing silane coupling agent to alumina, the mass ratio of the second solvent to alumina and / or the time of the ball milling reaction are different, as shown in Table 1 for details.

[0067] The alumina powders obtained in Examples 2-17 above with a silane coupling agent containing an amide group grafted on the surface thereof can all be represented by the following formula II:

[0068]

[0069] Among them, R1, R2, and R3 are each selected from one of H atom, alkane group, and alkoxy group, and at least one of R1 to R3 is an alkoxy group; R4 and R5 are each selected from one of straight chain or branched alkane group, and R is selected from one of straight chain or branched alkane group and aromatic group.

[0070] Comparative Example 1

[0071] The difference between this comparative example and Example 1 is that the aluminum oxide does not undergo the process of grafting modified silane coupling agent in steps S1-S2 of Example 1. In this comparative example, the packaging base product is prepared using aluminum oxide without grafting silane coupling agent, and the method for preparing the packaging base product is the same as that for preparing the packaging base product in Example 1, specifically:

[0072] A method for preparing a ceramic package base comprises the following steps:

[0073] (1) mixing alumina powder (the alumina powder is the same as the alumina powder before mixed and ball-milled in step S2 of Example 1), a sintering aid, a dispersant, a colorant, a resin and a third solvent in a mass ratio of 1:0.07:0.5:1.5:8:2 and ball-milling to obtain a ceramic slurry;

[0074] The sintering aid is a mixture of zirconium oxide, magnesium oxide, and yttrium oxide in a mass ratio of 1:0.5:0.2, the colorant is chromium oxide, the resin is acrylic resin, the dispersant is triolein, and the third solvent is a mixture of acetone and isopropanol in a mass ratio of 1:1;

[0075] (2) tape-casting the ceramic slurry to obtain a ceramic green body, and according to the structural requirements of different ceramic layers of the packaging base, respectively perform hole opening, hole filling, and printing of conductive patterns on each layer of the ceramic green body, and then stack the layers of the ceramic green body together and cut them into a plurality of ceramic packaging base green bodies;

[0076] (3) The ceramic package base green body is sintered at 1350° C. for 5 hours to form porcelain, and a metal layer is plated on the exposed conductive pattern to obtain a package base product.

[0077] Comparative Example 2

[0078] The difference between this comparative example and Example 1 is that the alumina-grafted silane coupling agent does not undergo the modification process of step S1 in Example 1, specifically:

[0079] A method for preparing aluminum oxide powder comprises the following steps:

[0080] 3-aminopropyltrimethoxysilane, acetone and alumina powder were mixed and reacted under ball milling at 300 rpm for 2 hours to obtain alumina powder grafted with 3-aminopropyltrimethoxysilane; wherein the mass ratio of 3-aminopropyltrimethoxysilane, acetone and alumina powder was 0.005:0.5:1.

[0081] A method for preparing a ceramic package base comprises the following steps:

[0082] (1) mixing the 3-aminopropyltrimethoxysilane grafted alumina powder, a sintering aid, a dispersant, a colorant, a resin and a third solvent in a mass ratio of 1:0.07:0.5:1.5:8:2 and ball milling at 300 rpm to obtain a ceramic slurry;

[0083] The sintering aid is a mixture of zirconium oxide, magnesium oxide, and yttrium oxide in a mass ratio of 1:0.5:0.2, the colorant is chromium oxide, the resin is acrylic resin, the dispersant is triolein, and the third solvent is a mixture of acetone and isopropanol in a mass ratio of 1:1;

[0084] (2) tape-casting the ceramic slurry to obtain a ceramic green body, and according to the structural requirements of different ceramic layers of the packaging base, respectively perform hole opening, hole filling, and printing of conductive patterns on each layer of the ceramic green body, and then stack the layers of the ceramic green body together and cut them into a plurality of ceramic packaging base green bodies;

[0085] (3) The ceramic package base green body is sintered at 1350° C. for 5 hours to form porcelain, and a metal layer is plated on the exposed conductive pattern to obtain a package base product.

[0086] Comparative Example 3

[0087] The difference between this comparative example and Example 1 is that the alumina-grafted silane coupling agent does not undergo the modification process of step S1 in Example 1, and the silane coupling agent is changed from 3-aminopropyltrimethoxysilane to 3-methacrylamidepropyltriethoxysilane, specifically:

[0088] A method for preparing aluminum oxide powder comprises the following steps:

[0089] 3-Methacrylamidopropyltriethoxysilane, acetone and alumina powder were mixed and reacted under ball milling at 300 rpm for 2 hours to obtain alumina powder grafted with 3-methacrylamidopropyltriethoxysilane; wherein the mass ratio of 3-methacrylamidopropyltriethoxysilane, acetone and alumina powder was 0.005:0.5:1.

[0090] A method for preparing a ceramic package base comprises the following steps:

[0091] (1) mixing the above-mentioned 3-methacrylamide propyl triethoxysilane grafted alumina powder, a sintering aid, a dispersant, a colorant, a resin and a third solvent in a mass ratio of 1:0.07:0.5:1.5:8:2 and ball milling to obtain a ceramic slurry;

[0092] The sintering aid is a mixture of zirconium oxide, magnesium oxide, and yttrium oxide in a mass ratio of 1:0.5:0.2, the colorant is chromium oxide, the resin is acrylic resin, the dispersant is triolein, and the third solvent is a mixture of acetone and isopropanol in a mass ratio of 1:1;

[0093] (2) tape-casting the ceramic slurry to obtain a ceramic green body, and according to the structural requirements of different ceramic layers of the packaging base, respectively perform hole opening, hole filling, and printing of conductive patterns on each layer of the ceramic green body, and then stack the layers of the ceramic green body together and cut them into a plurality of ceramic packaging base green bodies;

[0094] (3) The ceramic package base green body is sintered at 1350° C. for 5 hours to form porcelain, and a metal layer is plated on the exposed conductive pattern to obtain a package base product.

[0095] Comparative Example 4

[0096] The difference between this comparative example and Example 1 is that the alumina-grafted silane coupling agent does not undergo the modification process of step S1 in Example 1, and the silane coupling agent is changed from 3-aminopropyltrimethoxysilane to 3-mercaptopropyltriethoxysilane, specifically:

[0097] A method for preparing aluminum oxide powder comprises the following steps:

[0098] 3-Mercaptopropyltriethoxysilane, acetone and alumina powder were mixed and reacted under ball milling at 300 rpm for 2 hours to obtain 3-mercaptopropyltriethoxysilane grafted alumina powder; wherein the mass ratio of 3-mercaptopropyltriethoxysilane, acetone and alumina powder was 0.005:0.5:1.

[0099] A method for preparing a ceramic package base comprises the following steps:

[0100] (1) mixing the 3-mercaptopropyltriethoxysilane grafted alumina powder, a sintering aid, a dispersant, a colorant, a resin and a third solvent in a mass ratio of 1:0.07:0.5:1.5:8:2 and ball milling to obtain a ceramic slurry;

[0101] The sintering aid is a mixture of zirconium oxide, magnesium oxide, and yttrium oxide in a mass ratio of 1:0.5:0.2, the colorant is chromium oxide, the resin is acrylic resin, the dispersant is triolein, and the third solvent is a mixture of acetone and isopropanol in a mass ratio of 1:1;

[0102] (2) tape-casting the ceramic slurry to obtain a ceramic green body, and according to the structural requirements of different ceramic layers of the packaging base, respectively perform hole opening, hole filling, and printing of conductive patterns on each layer of the ceramic green body, and then stack the layers of the ceramic green body together and cut them into a plurality of ceramic packaging base green bodies;

[0103] (3) The ceramic package base green body is sintered at 1350° C. for 5 hours to form porcelain, and a metal layer is plated on the exposed conductive pattern to obtain a package base product.

[0104] Table 1

[0105]

[0106]

[0107]

[0108] The alumina powder, ceramic slurry, ceramic green body, and ceramic packaging base green body involved in the above embodiments and comparative examples were subjected to performance tests. The specific test methods and indicators are shown in Table 2 below, and the test results are shown in Table 3 below.

[0109] Table 2

[0110]

[0111]

[0112] Table 3

[0113]

[0114] Compared with Example 1, Example 1 did not graft the aluminum oxide, and the D50 of the aluminum oxide was too high, the slurry viscosity was too low, the strength of the green body and the cooked porcelain was insufficient, and the warpage was high. After the aluminum oxide in Example 1-17 was grafted with an amide-containing silane coupling agent, the D50 of the obtained powder decreased, the viscosity of the ceramic slurry was appropriate, the strength of the green body and the cooked porcelain was significantly improved, and the warpage of the cooked porcelain was reduced. Although Comparative Example 2 used 3-aminopropyltrimethoxysilane to modify the aluminum oxide, the silane coupling agent did not have an amide group, and the amino group at the end of the aminopropyltrimethoxysilane still had a certain hydrophilicity. The affinity of the grafted powder to the resin was insufficient, and it was difficult to improve the dispersibility and increase the ceramic strength. The silane coupling agent grafted on the surface of the alumina powder in Comparative Example 3 also contains an amide group, but the amide group is connected to the olefinic group, and is easy to crosslink (crosslinking between coupling agents and crosslinking with resin). The green body after casting is sticky, and it is not easy to peel off from the base tape after casting, and it is not easy to cut during cutting. The cutting process is easy to stick, the operation is difficult, and the dimensional accuracy is reduced. The surface of the alumina in Comparative Example 4 is grafted with 3-mercaptopropyltriethoxysilane, but the 3-mercaptopropyltriethoxysilane is difficult to hydrolyze and is difficult to graft on the surface of the alumina powder, which is not enough to improve the dispersibility and ceramic strength.

[0115] It can be seen from Example 1 and Example 2-5 that the chemical structure of the alumina powder grafted with silane coupling agent in Example 2-5 is as shown in Formula 1, and the grafted coupling agent structure contains both amino and amide groups, which has a good effect on improving the powder dispersibility of alumina and the strength of ceramic green bodies and cooked porcelain.

[0116] It can be seen from Examples 6-7 and 2-5 that the molecular weight of the grafted silane coupling agent has a certain influence on the powder dispersibility, green body and cooked porcelain strength, and slurry viscosity. The preferred relative molecular mass of the amide-containing silane coupling agent is 300-500.

[0117] It can be seen from Examples 2-5 and 8 that the number of carbon atoms in R, R4, and R5 in the alumina structure of Example 8 is smaller than that in Example 2-5, and the fired porcelain strength and warpage in Example 2-5 are better than those in Example 8. Therefore, the ratio of the number of carbon atoms in R4, R5, and R can be selected as n(R4):n(R5):n(R)=(0.08-0.6):(0.1-0.6):1, preferably (0.08-0.6):(0.13-0.54):1.

[0118] It can be seen from Examples 2 and 9-11 that the mass ratio of the amide-containing silane coupling agent to alumina has a certain influence on the viscosity of the ceramic slurry, the strength of the green and cooked porcelain, and the warpage. The mass ratio of the amide-containing silane coupling agent to alumina can be (0.001-0.007):1, preferably (0.001-0.005):1.

[0119] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A method for preparing aluminum oxide powder, characterized in that: The steps include: (1) mixing an amino-containing silane coupling agent with a first solvent, and then adding a carboxylic acid ester to react under the protection of an inert gas to obtain a silane coupling agent containing an amide group; the amino-containing silane coupling agent includes at least one of 3-aminopropyltrimethoxysilane, N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane, aminoethylaminomethylmethyldiethoxysilane, and N-(6-aminohexyl)aminomethyltriethoxysilane; the carboxylic acid ester includes at least one of isobutyl hexanoate, n-butyl decanoate, and isobutyl dodecanoate; the molar ratio of the amino-containing silane coupling agent to the carboxylic acid ester is 1:(0.5-1.5); (2) The silane coupling agent containing an amide group, a second solvent, and aluminum oxide are sequentially mixed and grafted to obtain the aluminum oxide powder; the mass ratio of the silane coupling agent containing an amide group to the aluminum oxide is (0.001-0.007):

1.

2. The method for preparing alumina powder according to claim 1, characterized in that: Include at least one of the following: In step (1), the molar ratio of the amino-containing silane coupling agent to the first solvent is (1-2): 1; In step (1), the reaction temperature is 75-90°C and the reaction time is 4-6h; In step (1), the first solvent includes at least one of n-butanol, isopropanol, and ethanol; In step (2), the grafting reaction is carried out under ball milling conditions, and the grafting reaction time is 2-3 hours; In step (2), the mass ratio of the second solvent to the aluminum oxide is (0.46-0.52): 1; In step (2), the second solvent includes at least one of acetone, ethanol, isopropanol, and terpineol.

3. Alumina powder obtained by the method for preparing alumina powder according to claim 1 or 2, characterized in that: The surface of the aluminum oxide powder is grafted with a silane coupling agent containing an amide group.

4. Use of the alumina powder according to claim 3 in preparing a ceramic packaging base.

Citation Information

Patent Citations

  • Bonding sheet, and cutting / chip bonding film

    CN104212375A

  • Functional magnetic powder and preparation method thereof, magnetic nylon master batch and preparation method thereof, and magnetic plastic material

    CN117510991A